Evaluation of GRHPR Enzyme and some Biochemical Variables in Patients with Calcium Oxalate Kidney Stone Disease - Abed Almuhssen Alzubaidy, Duha; Hassan Alwan Al Obaidy, Luma (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
Kidney stone disease is a highly significant clinical issue that poses a serious threat to both global health and the economy. For the sustainability of good health and well-being of kidney stone patients, this study aimed to elucidate the role of the enzyme glyoxylate reductase and hydroxypyruvate reductase (GRHPR) in the formation of the kidney stones and their development. There are many different types of kidney stones, but calcium oxalate kidney stones are the most prevalent in Iraq. In this study, 50 Iraqi patients with calcium oxalate stones (25 males and 25 females) were compared to 30 healthy control groups (17 males and 13 females). The biochemical tests for kidney function, such as serum urea, creatinine, and uric acid, were detected in the sera of both study groups. In addition to fasting blood sugar (FBS), Ca++, Na+, complete blood count (CBC) and blood group tests, Urine was collected for General Urine Examination (GUE), to visualize oxalate crystals in the patient’s urine. Also, the relationship between the concentration of the enzymes glyoxylate reductase and hydroxypyruvate reductase (GRHPR) and the development of calcium oxalate kidney stones in Iraqi patients and the control group was examined. It was found that the enzyme concentrations in the control group were (4.78 ± 1.06 mg/dl) significantly higher than the enzyme concentration in the patients group  (0.411 ± 0.02 mg/dl). Also, it was found ,  that the uric acid  concentrations were within the normal range for both groups, but urea and creatinine were significantly higher in kidney stone  patients, while they were at the normal ranges in the control group.